2012
DOI: 10.1603/ec12069
|View full text |Cite
|
Sign up to set email alerts
|

Retail Firewood Can Transport Live Tree Pests

Abstract: Untreated firewood can harbor destructive insects and pathogens and transport them to uninfested areas. In a national survey of retail locations selling firewood in 18 states, over half (52%) of the firewood was from sources out of the purchase state and 50% showed evidence of insect infestation. In a three state survey of southern Rocky Mountain retailers, the most common retailer types carrying firewood were grocery stores and department or big box stores followed by gas stations or convenience stores. In 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The transport of raw and processed wood products like logs, firewood, timber, lumber, and wood packaging materials has been responsible for the dispersal of many insects from different orders (e.g., Roques and Auger-Rozenberg 2006;Jacobi et al 2012). Special attention has been paid to the arrival and spread of bark and wood-boring insects that represent serious ecological and economic threats to forests health (e.g., Smith et al 2004;Muirhead et al 2006;Boissin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of raw and processed wood products like logs, firewood, timber, lumber, and wood packaging materials has been responsible for the dispersal of many insects from different orders (e.g., Roques and Auger-Rozenberg 2006;Jacobi et al 2012). Special attention has been paid to the arrival and spread of bark and wood-boring insects that represent serious ecological and economic threats to forests health (e.g., Smith et al 2004;Muirhead et al 2006;Boissin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Here again, firewood transport has been suspected in the spread of A. coxalis from either Arizona or northern Mexico to California (Coleman and Seybold 2008). In a recent US survey of firewood retailers, live insects emerged from almost 50% of around 400 firewood bundles analyzed (Jacobi et al 2012). This is not surprising as firewood is commonly cut from stressed, dying or recently dead trees, which often harbor various insects and diseases (Hanks 1999;Lieutier et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Untreated firewood is known to harbor a variety of organisms, particularly bark- and wood-infesting insects [20]. Perhaps most notably, firewood movement has been linked to the spread of two destructive alien insects, the Asian longhorned beetle ( Anoplophora glabripennis (Motschulsky)) and the emerald ash borer ( Agrilus planipennis Fairmaire), in both urban and natural forests in the eastern US and Canada [7], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found live bark- and wood-boring insects ( = borers) in 23% of the firewood pieces, and an additional 41% displayed evidence of prior borer infestation. Jacobi et al [20] purchased more than 400 bundles of firewood from retailers in the US states of Colorado, New Mexico, Utah, and Wyoming during a three-year period (2007–2009). Caging the firewood to measure insect emergence, they reported that live insects emerged from 47% of the bundles over 18 months of rearing time, with an average of 11 insects emerging from each infested bundle.…”
Section: Introductionmentioning
confidence: 99%
“…Invading species are often dispersed through movement of wood products, nursery stock, and Þrewood (Yates et al 1981, Galford 1984, Haack et al 2010, Jacobi et al 2012. In California, wood borers (Buprestidae and Cerambycidae) in cut wood account for the majority of insects detected at regulatory border stations (Bokach et al 2011).…”
mentioning
confidence: 99%